Bacterial and fungal cometabolism of 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane (DDT) and its breakdown products. - Subba-Rao, R V (1985)
Resting cells of bacteria grown in the presence of diphenylmethane oxidized substituted analogs such as 4-hydroxydiphenylmethane, bis(4-hydroxyphenyl)methane, bis(4-chlorophenyl)methane (DDM), benzhydrol, and 4,4'-dichlorobenzhydrol. Resting cells of bacteria grown with benzhydrol as the sole carbon source oxidized substituted benzhydrols such as 4-chlorobenzhydrol, 4,4'-dichlorobenzhydrol, and other metabolites of 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane (DDT), such as DDM and bis(4-chlorophenyl)acetic acid. Bacteria and fungi converted 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane to 1,1-dichloro-2,2-bis(4-chlorophenyl)ethylene, 1,1-dichloro-2,2-bis(4-chlorophenyl)ethane, DDM, 4,4'-dichlorobenzhydrol, and 4,4'-dichlorobenzophenone. Aspergillus conicus converted 55% of bis(4-chlorophenyl)acetic acid to unidentified or unextractable water-soluble products. Aspergillus niger and Penicillium brefeldianum converted 12.4 and 24.6%, respectively, of 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane to water-soluble and unidentified products. 4-Chlorophenylacetic acid, a product of ring cleavage, was formed from DDM by a false smut fungus of rice. A. niger converted 4,4'-dichlorobenzophenone to 4-chlorobenzophenone and a methylated 4-chlorobenzophenone.